Plasma polychlorobiphenyl and organochlorine pesticide level and risk of major lymphoma subtypes. Issue 2 (15th August 2007) - Cocco, P; Brennan, P; Ibba, A; de Sanjosé Llongueras, S; Maynadié, M; Nieters, A; Becker, N; Ennas, M G; Tocco, M G; Boffetta, P
Abstract : Background: There is conflicting epidemiological evidence concerning an increase in risk of non-Hodgkin's lymphoma (NHL) associated with elevated blood levels of persistent organochlorine (OC) pesticides and polychlorobiphenyls (PCBs). Methods: We measured the concentration of 17 OC pesticides, including hexachlorobenzene (HCB), four lindane isomers (α-, β-, γ- and δ-hexachlorocyclohexane (HCH)), two chlordane species (heptachlor and oxy-chlordane), four cyclodiene insecticides (aldrin, dieldrin, endrin and mirex), six dichloro-diphenyl-trichloroethane (DDT) isomers and nine PCB congeners (PCBs 28, 52, 101, 118, 138, 153, 170, 180 and 194) in plasma samples of 377 subjects, including 174 NHL cases and 203 controls from France, Germany and Spain. The risk of NHL and its major subtypes associated with increasing blood levels of OC pesticides and PCBs was calculated using unconditional logistic regression. Results: Risk of NHL, diffuse large B cell lymphoma (DLBCL) and chronic lymphatic leukaemia (CLL) did not increase with plasma levels of HCB, β-HCH, p, p′ -dichloro-diphenyl-dichloroethylene (DDE), or total and individual PCBs or their functional groups, in the overall study population. Substantial heterogeneity in DLBCL risk associated with immunotoxic PCBs (p = 0.03) existed between the Spanish subgroup (odds ratio (OR) for immunotoxic PCB plasma level above the median vs below the median was 0.7, 95% CI 0.3 to 1.6) and the French and German subgroups combined (OR 3.2, 95% CI 0.9 to 11.5). Conclusion: We did not find evidence of an association between NHL risk and plasma level of OC pesticides and PCBs.